2023
DOI: 10.1111/joss.12881
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of individual factors influencing self‐reported household food waste in Australia

Ana Gimenez,
Gastón Ares,
Sara R. Jaeger

Abstract: Food losses and waste (FLW) is a global problem. Because household FLW is one of the biggest contributors to total FLW, strategies are being implemented to reduce per capita FLW in many countries. The present research contributed to this goal by investigating individual factors influencing self‐reported household food waste in Australia. Using a web survey, data were obtained from 847 consumers. The average per capita food waste corresponded to 339 g/week and the median to 180 g/week. The most frequently waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Paroissien et al, in a study of the French population, found that the opportunity cost of time increases the frequency of food waste by households [35]. Age, household size, and numerous psychological factors, among a myriad of other influences, have also been linked to household food waste [36]. Focusing interventions on those consumer segments with higher propensities to waste food may assist with preventative measures [37].…”
Section: Discussionmentioning
confidence: 99%
“…Paroissien et al, in a study of the French population, found that the opportunity cost of time increases the frequency of food waste by households [35]. Age, household size, and numerous psychological factors, among a myriad of other influences, have also been linked to household food waste [36]. Focusing interventions on those consumer segments with higher propensities to waste food may assist with preventative measures [37].…”
Section: Discussionmentioning
confidence: 99%